The Effect Of Profitability, Debt To Equity Ratio, Earning Per Share Ratio And Price To Book Value Ratio On Stock Price Of LQ45 Index - Meigawati, Evelyn; Putri, Arie Pratania; Purba, Rahima Br (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Stock market index is an indicator that summarizes stock market information and the performance of various stocks traded in an exchange. The LQ45 index consists of 45 stocks with the highest level of liquidity and the largest market capitalization on the Indonesia Stock Exchange (IDX), which selected on certain criteria. In making investment decisions, investors need information about stock price fluctuations in order to assess the feasibility of a stock. Therefore, access to accurate data on the company’s financial performance is important including profitability, debt to equity ratio, earning per share ratio, and price to book value ratio. This research uses the population of companies in the LQ45 index on IDX during 2021-2023 period. The selection of population was based on the index’s ability to maintain stock price stability, despite unfavorable market conditions during that period. Samples were selected using a non-probability sampling method with purposive sampling technique, resulting in a total of 24 companies with 72 research samples. The results showed that profitability, debt to equity ratio, earning per share ratio, and price to book value ratio each have a significant influence on stock price. In addition, simultaneously, the four variables also have a significant effect on stock price.